Modelling mastication and aroma release from white rice during food oral processing - How, Syahmeer; Jones, Jim R.; Morgenstern, Marco P.; Gray-Stuart, Eli; Bronlund, John E.; Saint-Eve, Anne; Cristian Trelea, Ioan; Souchon, Isabelle (Elsevier, 2023)
A mathematical model describing the aroma release from white rice during food oral processing (FOP) was developed based of a coupled selection-breakage and mass transport models. An integrated selection and breakage model was able to predict the changes of bolus surface area over time, assuming that the pasted portion of masticated rice particles was the dominant mechanism when aroma was released to the liquid bolus during chewing. Model predictions were validated against experimental data for all subjects when the input parameters were directly obtained from the coupled chewing-aroma release model. Adjusting the input parameters from the validated coupled model showed that the portion size, initial concentration of the studied aroma compound, initial liquid volume and the rice pasted fraction were the most sensitive product-related parameters. The oral cavity volume, pharynx volume, nasal cavity volume and the breathing frequency were the most sensitive physiological parameters. The physico-chemical parameter which had the most significant effect was the mass transfer coefficient in the saliva phase.